Oswald de Andrade: da "deglutição antropofágica" à "revolução comunista" (1923-1937) - Valdeci da Silva Cunha (2012)
This paper intended to study the political and ideological trajectory of Oswald de Andrade, mainly during the period of his ideological turnover between the 1920s and 1930s when the writer made his choice for the communist militancy. Several kinds of sources were analyzed among them manifestos, newspaper articles, interviews, autobiographical reports, and excerpts of his literary works in the attempt to understand his intellectual development, in the context of the political and social struggles characteristic to that period. By using the concepts of political and intellectual culture, we realized the functionality and limits of its uses to analyze Oswald de Andrades acts and political representations. By analyzing the trajectory of a communist intellectual but not away from the periods so called cultural Cannibalism we triedto recollect the polemical events Andrade was involved, mainly in relation to the orthodoxy of the Brazilian Political Party, what was incompatible to his intention of being independent as a militant. Among the proposals of social revolution and the enthusiasm of creating Brazilian Art and Literature of that time, Andrade stood out as an intellectual since the 1920s, attentive to the growing of authoritarianism in Brazil, and opposed to any kind of fascist ideals.